2004
DOI: 10.1152/physrev.00026.2003
|View full text |Cite
|
Sign up to set email alerts
|

Pleural Mechanics and Fluid Exchange

Abstract: Lai-Fook, Stephen J. Pleural Mechanics and Fluid Exchange. Physiol Rev 84: 385–410, 2004; 10.1152/physrev.00026.2003.—The pleural space separating the lung and chest wall of mammals contains a small amount of liquid that lubricates the pleural surfaces during breathing. Recent studies have pointed to a conceptual understanding of the pleural space that is different from the one advocated some 30 years ago in this journal (Agostoni E. Physiol Rev 52: 57–128, 1972). The fundamental concept is that pleural surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(81 citation statements)
references
References 196 publications
(300 reference statements)
4
72
0
5
Order By: Relevance
“…Trying to overcome the aforementioned we have previously shown that sheep pleural tissue appears to be similar and relative to human in terms of pleural electrophysiology (Hatzoglou et al 2001, Kouritas et al 2008, 2010a, 2010b and its alterations by other hormones such as insulin (Kouritas et al, 2010). This observation is consistent with the fact that various species present similar pleural physiology properties depending on their visceral pleura thickness as is the case for sheep and humans (Lai-Fook, 2004). The effect of histamine in the electrophysiology of sheep visceral and parietal pleura is currently underway.…”
Section: Page 13 Of 26supporting
confidence: 83%
See 2 more Smart Citations
“…Trying to overcome the aforementioned we have previously shown that sheep pleural tissue appears to be similar and relative to human in terms of pleural electrophysiology (Hatzoglou et al 2001, Kouritas et al 2008, 2010a, 2010b and its alterations by other hormones such as insulin (Kouritas et al, 2010). This observation is consistent with the fact that various species present similar pleural physiology properties depending on their visceral pleura thickness as is the case for sheep and humans (Lai-Fook, 2004). The effect of histamine in the electrophysiology of sheep visceral and parietal pleura is currently underway.…”
Section: Page 13 Of 26supporting
confidence: 83%
“…Histamine decreases the PD in nostrils (Yang et al 2003) and in blood brain barrier (Hurst andClark, 1998, Butt, 1995) while it increases Cl -conductance and induces K + permeability and Ca 2+ entry via nitric oxide production in vascular cells (Groschner et al 1994). In pleura, histamine influences permeation through cells, given that, since the pleura is considered 'leaky', the paracellular pathway offers unrestricted passage for solutes (Lai-Fook, 2004, Hatzoglou et al 2001). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] Starling's hypothesis; [2] Fick's law of diffusion; [3] the serosal pressure associated with organ movement and posture; [4] active transport by mesothelial cells; and [5] a lymphatic drainage system via lymphatic stomata (30,31). Of these factors, the lymphatic drainage system via lymphatic stomata likely plays an important role (30)(31)(32)(33)(34), which may contribute up to approximately 75-80% of the fluid absorption rate in the abdominal and pleural cavities (33,35).…”
Section: Serosal Membranes Lymphatic Stomata and Coelomic Fluid Draimentioning
confidence: 99%
“…Of these factors, the lymphatic drainage system via lymphatic stomata likely plays an important role (30)(31)(32)(33)(34), which may contribute up to approximately 75-80% of the fluid absorption rate in the abdominal and pleural cavities (33,35).…”
Section: Serosal Membranes Lymphatic Stomata and Coelomic Fluid Draimentioning
confidence: 99%